Penelitian Serabut Kelapa Sebagai Material Lantai Ecofriendly dan Biodegradable - Marcel Bondra; Andereas Pandu Setiawan; Poppy Firtatwentyna Nilasari (Intra, 2018)
Indonesia is the biggest coconut producing country in the world. The number of coconut fibers produced in Indonesia for a year can reach 18 million tons, but only 3% is used. This research aims to expand the use of coconut fiber material. The purpose of this research is to utilize existing materials to be more utilized. Moreover, this research also aims to produce environmentally friendly materials in order to reduce the use of synthetic materials. This research is an experimental method to find suitable treatment and material using coconut fiber. The variables involved in this study relate to things such as adhesive types, fiber sizes, and thickness of finished material. The adhesives used are ecofriendly adhesives, so they won’t damage the nature at the time of production nor at the time of disposal. From this study, it was found that by using a mixture of starch glue with short coconut fibers, the results were the strongest and has the most density among the other experiments. The results of this study indicate that the material produced with a mixture of starch and coconut fibers has advantages in terms of weight, strength, flexibility, as well as bumps and fire resistance. Therefore, other than used as floor material, this material can also be used as wall and ceiling panel as well.